Uji Daya Hambat Sediaan Gel Ekstrak Etanol Daun Mangga Arum Manis (Mangifera indica Linn.) Terhadap Pertumbuhan Staphylococcus epidermidis - Maulana, Maulana Zulkarnain Imansyah (Akademi Farmasi Yamasi Makassar, 2024)
The compounds contained in the leaves of the arum manis mango (Mangifera indica LINN.) are tannins, alkaloids, saponins, flavonoids and mangiferin which have antibacterial properties. This study aims to determine whether the ethanol extract gel preparation of mango arum manis (Mangifera indica LINN.) leaves has antibacterial inhibition against Staphylococcus epidermidis. Mango arummanis leaf extract was prepared in a gel preparation with a concentration of 15%, 20% and 25%. Testing the antibacterial activity of mango arummanis (Mangifera indica LINN.) leaf extract gel using the paperdisk method and agar medium (NA) as a medium and incubated for 1x24 hours at 37oC. Then observations were made by measuring the inhibition zone that occurred at each preparation concentration on the Staphylococcus epidermidis test bacteria. The results showed that the inhibition zone of the ethanol extract gel preparation of Mango Arum Manis (Mangifera indica LINN.) concentration of 15% showed an inhibition zone diameter of 5.03 mm, a concentration of 20% showed an inhibition zone diameter of 6.28 mm, a concentration of 25% showed an inhibition zone diameter of 7.04 mm with the results of inhibition of bacterial growth categorized as moderate (5-10mm). Whereas in the positive control of clindamycin ointment, the diameter of the inhibition zone was 26.59 mm with the result that the inhibition of bacterial growth was categorized as very strong. The conclusion of the study stated that the ethanol extract of mango arummanis leaves (Mangifera indica LINN.) with a concentration of 25% was better than concentrations of 15% and 20%.